Prevalence, characteristics, and reporting of adverse drug reactions in an Australian hospital: a retrospective review of hospital admissions due to adverse drug reactions. Issue 10 (3rd October 2021) - Li, Raymond; Curtis, Kate; Zaidi, Syed Tabish Razi; Van, Connie; Thomson, Amy; Castelino, Ronald
ABSTRACT: Background : Adverse drug reaction (ADR) related hospitalizations is a major cause of morbidity and mortality in Australia. This study investigated the prevalence, characteristics, and reporting of ADR related hospitalizations at a tertiary hospital in Australia. Research design and methods : A retrospective review of all ADR related hospitalizations from October to December 2019 was conducted using eMedical Records. They were classified by medicine class, ADR type, preventability, and the strength of causal relationship. ADRs were searched within the regulator's safety database to verify whether it was reported. Results : A total of 496 ADR related hospitalizations were identified from 5521 records (9.0%). Nervous system agents (32.3%) were responsible for most ADR hospitalizations and were more likely to cause psychiatric disorders (RR 9.71, 95%CI 4.98–18.87). They were also more likely to cause preventable ADRs (HR 1.62, 95%CI 1.46–1.81). Patient age (OR 1.04, 95%CI 1.03–1.05) and the number of medicines (OR 1.13, 95%CI 1.11–1.15) were associated with ADR related hospitalizations. Under-reporting to the national regulator was over 99%. Conclusions : ADR under-reporting is highly prevalent in Australian hospitals. Further research into identifying specific barriers toward reporting ADRs are needed to inform strategies with a focus on healthcare professionals involved in prescribing, dispensing, and administrating nervous system agents.